Биоморфологические особенности форм Vicia faba L. в условиях Донбасса - Горлачева, З.С. (Промышленная ботаника, 2002)
The seed productivity of the two newly-introduced into Donbass vegetable forms of legumes having high potential and a relatively good real productivity of fruitage and seedage under the conditions of the insufficient water-supply has been studied. The lowest and the middle sections of the generative sphere formed at the IV–V stages of organogenesis proved to be the most productive.